Partner Phubbing and Relationship Satisfaction among High and Low Reward Romantic Partners: An Expectancy Violations Theory Perspective - Roberts, James A.; David, Meredith E. (International journal of human-computer interaction, 2024)
Partner phubbing (phone snubbing) is the perceived extent to which an individual uses or is distracted by his or her cellphone while in the company of his/her relationship partner. The present research examines the impact of partner phubbing on relationship satisfaction through an Expectancy Violations Theory perspective. Across two studies, including a survey of 180 adults currently in a romantic relationship, and an experiment of 141 married adults, results reveal that partner phubbing results in negative expectancy violations, which in turn lower relationship satisfaction. However, support is found for moderated mediation, such that the negative indirect effect of partner phubbing on relationship satisfaction depends on the phubber's level of partner reward value. When partner reward value is low, expectancy violations from partner phubbing have a strong negative effect on relationship satisfaction, but this effect is attenuated to non-significance when partner reward value is high.